(3QhM Gdbje hMQjI GdeaGgje (B:s (3fMh GdSjQ dEYGOI GdJQGHW hGdJcGed Hjf efXheI Gdbje hGdYdhe GdGLJeGYjI (B/s - (3HdYbQhR, YHO GdQRGb,s 1981- ((3HjQhJ (B:s (3GdeDSSI GdYQHjI ddacQ hGdEHOGY,s, 2017)
(3gPG GdcJGH OQGSI adSajI aj GTJbGb GdeaGgje hGdbje GdeQJHWI HgG hNGUI eaghe GdYbd hJWhQg JHYG ddebGQHGJ GdefgLjI GdadSajI GdJj JJfGhdg hgj JMGhd GdGfJbGd HGdYbd ef Vjb GdeaGgje GdYdejI GdQjGVjI GdOjcGQJjI GdUGQeI Edi QMGHI Gdbje GdQhMjI hGdeYfhjI hGdYGWajI hGJSGYgG hJOd GdOQGSI Ydi JeQS eDdagG HefGgL GdfXQ GdadSajI eJeKdG ddeaGUd GdcHQi aj JWhQ eaghe GdYbd aj GdadSaI GdChQhHjI hGdOQGSI ecJhHI HdZI hGVMI hCSdhH Ydej Objb(B. s
(3HHdjhLQGajI (B: (3UaMI (B281-294.s
Keywords: (3Gdbje (B((3adSaI(B)s -- (3adSaI GdCNdGbs; (3Gdbjes -- (3LhGfH GLJeGYjIs